Uniform Confidence Bands for Local Polynomial Quantile Estimatorsâˆ—. (25th July 2014) - Sabbah, Camille
<x content-type="archive" xml:space="preserve">Abstract</x> This paper deals with uniform consistency and uniform confidence bands for the quantile function and its derivatives. We describe a kernel local polynomial estimator of quantile function and give uniform consistency. Furthermore, we derive its maximal deviation limit distribution using an approximation in the spirit of Bickel and Rosenblatt [P.J. Bickel and M. Rosenblatt, Ann. Statist. 1 (1973) 1071â€"1095].